1998
DOI: 10.1046/j.1523-1747.1998.00259.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of μ-Opiate Receptor in Human Epidermis and Keratinocytes

Abstract: There is increasing evidence that neurotransmitters play a crucial role in skin physiology and pathology. The expression and production of proopiomelanocortin molecules such as beta-endorphin in human epidermis suggest that an opiate receptor is present in keratinocytes. In this paper we show that human epidermal keratinocytes express a mu-opiate receptor on both the mRNA level and the protein level. Performing polymerase chain reaction with cDNA libraries from human epidermal keratinocytes gave the polymerase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
84
2
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(92 citation statements)
references
References 21 publications
5
84
2
1
Order By: Relevance
“…Figure 1a demonstrates the expression of µ-opiate receptor in the suprabasal layers of normal epidermis as it was shown before [3]. The µ-opiate receptor expression in epidermis of atopic dermatitis, shown in figure 1b, reveals a significant downregulation of this receptor.…”
Section: Resultsmentioning
confidence: 54%
See 1 more Smart Citation
“…Figure 1a demonstrates the expression of µ-opiate receptor in the suprabasal layers of normal epidermis as it was shown before [3]. The µ-opiate receptor expression in epidermis of atopic dermatitis, shown in figure 1b, reveals a significant downregulation of this receptor.…”
Section: Resultsmentioning
confidence: 54%
“…We have previously demonstrated that human epidermal keratinocytes express the µ-opiate receptor at both the mRNA and protein levels [3]. The µ-opiate receptor is expressed in all layers of the epidermis.…”
Section: Introductionmentioning
confidence: 99%
“…Immunohistochemistry studies in the skin have demonstrated the presence of multiple neuropeptides, neurotransmitters, and neurohormones in sensory nerves including substance P (SP), neurokinin A (NKA) (180), neurotensin, CGRP, VIP, pituitary adenylate cyclase activating polypeptide (PACAP) (549,809), peptide histidine-isoleucinamide (PHI), NPY (380), somatostatin (SST) (76), ␤-endorphin, enkephalin, galanin, dynorphin, secretoneurin, ACh, epinephrine, norepinephrine (NE), ␣-or ␥-melanocyte-stimulating hormone (MSH) (386, 497), and corticotropin-releasing hormone (CRH) (64,240,743,768,769,845). Colocalization of distinct neuropeptides can be observed in different tissues including the skin.…”
Section: B Cutaneous Neuropeptides and Neuropeptide Receptor Biologymentioning
confidence: 99%
“…3,4) These reports indicate that the MOR agonists are useful analgesics in the periphery, especially against the inflammatory tissues.…”
mentioning
confidence: 99%